Association Between Profound Shock Signs and Peripheral Intravenous Access Success Rates in Trauma Patients in the Prehospital Scenario: A Retrospective Study. (14th April 2023) - Barsky, Daniel; Radomislensky, Irina; Talmy, Tomer; Gendler, Sami; Almog, Ofer; Avital, Guy
Abstract : BACKGROUND: Hemorrhage is the leading cause of preventable death in trauma patients, and establishment of intravenous (IV) access is essential for volume resuscitation, a key component in the treatment of hemorrhagic shock. IV access among patients in shock is generally considered more challenging, although data to support this notion are lacking. METHODS: In this retrospective registry-based study, data were collected from the Israeli Defense Forces Trauma Registry (IDF-TR) regarding all prehospital trauma patients treated by IDF medical forces between January 2020 and April 2022, for whom IV access was attempted. Patients younger than 16 years, nonurgent patients, and patients with no detectable heart rate or blood pressure were excluded. Profound shock was defined as a heart rate >130 or a systolic blood pressure <90 mm Hg, and comparisons were made between patients with profound shock and those not exhibiting such signs. The primary outcome was the number of attempts required for first IV access success, which was regarded as an ordinal categorical variable: 1, 2, 3 and higher and ultimate failure. A multivariable ordinal logistic regression was performed to adjust for potential confounders. Patients' sex, age, mechanism of injury and best consciousness level, as well as type of event (military/nonmilitary), and the presence of multiple patients were included in the ordinal logistic regression multivariable analysis model based on previous publications. RESULTS: Five hundred thirty-seven patients were included, 15.7% of whom were recorded as having signs of profound shock. Peripheral IV access establishment first attempt success rates were higher in the nonshock group, and there was a lower rate of unsuccessful attempts in this group (80.8% vs 67.8% for the first attempt, 9.4% vs 16.7% for the second attempt, 3.8% vs 5.6% for the third and further attempts, and 6% vs 10% unsuccessful attempts, P = .04). In the univariable analysis, profound shock was associated with requirement for an increased number of IV attempts (odds ratio [OR], 1.94; confidence interval [CI], 1.17–3.15). The ordinal logistic regression multivariable analysis demonstrated that profound shock was associated with worse results regarding primary outcome (adjusted odds ratio [AOR], 1.84; CI, 1.07–3.10). CONCLUSIONS: The presence of profound shock in trauma patients in the prehospital scenario is associated with an increased number of attempts required for IV access establishment.